2020
DOI: 10.1111/nan.12667
|View full text |Cite
|
Sign up to set email alerts
|

Invited Review: The spectrum of neuropathology in COVID‐19

Abstract: There is increasing evidence that patients with Coronavirus disease 19 (COVID‐19) present with neurological and psychiatric symptoms. Anosmia, hypogeusia, headache, nausea and altered consciousness are commonly described, although there are emerging clinical reports of more serious and specific conditions such as acute cerebrovascular accident, encephalitis and demyelinating disease. Whether these presentations are directly due to viral invasion of the central nervous system (CNS) or caused by indirect mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
157
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(170 citation statements)
references
References 57 publications
6
157
0
7
Order By: Relevance
“…Clinically, symptoms are dysphoria, headache, delirium, confusion, mental disorder, loss of consciousness, and coma in severe cases. This histopathological pattern seems to be the most common correlate in COVID-19 patients with clinical CNS involvement [ 116 ].…”
Section: Resultsmentioning
confidence: 99%
“…Clinically, symptoms are dysphoria, headache, delirium, confusion, mental disorder, loss of consciousness, and coma in severe cases. This histopathological pattern seems to be the most common correlate in COVID-19 patients with clinical CNS involvement [ 116 ].…”
Section: Resultsmentioning
confidence: 99%
“…The most definitive means to assess for viral neuroinvasion in patients with COVID-19 is via neuropathology studies. In a review of 81 postmortem neuropathological examinations, Al-Sarraj et al concluded that it was difficult to parse out whether the findings were the result of viral neuroinvasion, hypoxia, multiorgan failure, cytokine storming, reduced immune response or strokes; they recommended the need for large-scale molecular and cellular investigations of brain tissue and CSF in conjunction with data on the neurological evaluation and neuroimaging for each patient [ 284 ]. Notably, Paniz-Mondolfi reported the presence of SARS-CoV-2 identified in brain tissue via ultrastructural analysis and molecular testing despite a negative SARS-CoV-2 PCR in CSF [ 285 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the distribution of cortical abnormalities was non-specific and could affect all lobes (15). Anosmia is a common neurological symptom of COVID-19 (41). The neuroimaging findings of COVID-19 patients with anosmia involved asymmetric olfactory bulbs on spin echo MRI, hyperintensities inside bilateral olfactory bulbs on T2 MRI with fat suppression and FLAIR, as well as normal MRI images (42)(43)(44).…”
Section: Other Abnormal Neuroimaging Findingsmentioning
confidence: 99%